Effectiveness of Levofloxacin in Community Acquired Pneumonia in Adult Bangladeshi Population (Medicine Today, 2016)
Community- acquired pneumonia (CAP) is a common condition with a significant mortality. Levofloxacin is recommended for the empiric management of CAP in inpatienst and outpatients. The present study conducted to find out the effectiveness of Levofloxacin in CAP among Bangladeshi Population. Total 50 Patients aged more than 18 years, diagnosed pneumonia based upon clinical features of respiratory tract infection and rediological changes, were included in this study. The study consists of four visits: first one for screening and enrollment. Second visit on day 2-4 during which patient on therapy, third visit 5-7 day after the last dose of the drug and fourth visit 28days after the last dose of the drug. The mean # SD of age of the respondents was 34.3# 19.1 years with a range of 18-100 years. Among the respondents 62.0% were male and 38.0% were female. Most of the respondents presented with fever (98.0%) and cough (100.0%) and chest pain was present in 66.0% cases. Ninety six percent respondents presented with productive cough and only 4.0% respondents with dry cough. Consolidation in left lower zone was the most common findings (32.0%) followed by consolidation in right mild zone (30.0%). Among the respondents 32.0% were treated with oral form and 68.0% were treated with injectable form of levofloxacin. About 92.0% were improved with the treatment. Levofloxacin monotherapy is well tolerated, cost-effective treatment for patients with CAP. Further large scale multi- centered study will help to strengthen this outcomeMedicine Today 2015 Vol.27(2): 9-13